2022
DOI: 10.1039/d1ra06439h
|View full text |Cite
|
Sign up to set email alerts
|

Phenylalanyl tRNA synthetase (PheRS) substrate mimics: design, synthesis, molecular dynamics and antimicrobial evaluation

Abstract: Nineteen novel compounds were designed to mimic Phe-AMP, as a new hope to find novel antibacterial agents and combat the antibiotic resistance. E. faecalis PheS homology model was constructed to study the mimics–enzyme interactions in more detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Docking and molecular dynamics simulations were performed as previously described [ 75 , 76 ]. Docking studies, using the constructed model, were performed to generate protein–ligand complexes, using MOE [ 28 ] until a RMSD gradient of 0.01 kcal mol −1 Å −1 with the MMFF94 forcefield (ligands) and partial charges were automatically calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Docking and molecular dynamics simulations were performed as previously described [ 75 , 76 ]. Docking studies, using the constructed model, were performed to generate protein–ligand complexes, using MOE [ 28 ] until a RMSD gradient of 0.01 kcal mol −1 Å −1 with the MMFF94 forcefield (ligands) and partial charges were automatically calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Molecular docking and molecular dynamics simulations were performed as previously described. 25,26 Briefly docking studies, using the crystal structure of Mtb CYP121A1 co-crystallised with cYY (pdb 4 ) were performed to generate PDB Mtb CYP121A1–ligand complexes, using MOE 22 until a RMSD gradient of 0.01 kcal mol −1 Å −1 with the MMFF94 forcefield (ligands) and partial charges were automatically calculated. The charge of the haem iron at physiological pH was set to 3 + (geometry d 2 sp 3 ) through the atom manager in MOE.…”
Section: Methodsmentioning
confidence: 99%
“…The parameters such as bond angles and bond lengths generated after optimization is given in Table S1. Based on the Periodic Bond Chain (PBC) crystal data, it is revealed that compound TC is orthorhombic [34] having space group P222 1 and cell dimensions; a = 16.7237 Å, b = 11.1801 Å and c = 8.8999 Å having α = β = γ = 90°.…”
Section: Molecular Geometrymentioning
confidence: 99%